2007
DOI: 10.1517/14740338.6.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Methadone-associated long QT syndrome: improving pharmacotherapy for dependence on illegal opioids and lessons learned for pharmacology

Abstract: Methadone is used as the pharmacologic mainstay for substitution for illegal opiates and as analgesic for chronic or cancer-related pain. Given the benefits of methadone substitution for illicit opioids, the finding of an association between methadone and prolongation of cardiac depolarization (QT prolongation) and torsades de pointes is of great concern. QT prolongation can occur with many drugs and is a potentially lethal adverse drug reaction, necessitating risk monitoring and therapeutic alternatives in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 116 publications
0
28
0
1
Order By: Relevance
“…Although most early studies suggested that the methadone-induced QTc prolongation is dose dependent, the dosage range of methadone required to induce clinically significant QTc prolongation remains unclear (Ehret et al, 2007;Ehret et al, 2006;Kim and Manini, 2008;Piguet et al, 2004;Reddy et al, 2010). Other risk factors such as the concurrent use of CYP450 isoenzyme inhibitors and hepatic insufficiency, which result in an increase in the plasma concentration of methadone, have also been suggested to contribute to QTc prolongation (Piguet et al, 2004).…”
Section: Cyp2c19 Gene In Methadone Maintenancementioning
confidence: 99%
“…Although most early studies suggested that the methadone-induced QTc prolongation is dose dependent, the dosage range of methadone required to induce clinically significant QTc prolongation remains unclear (Ehret et al, 2007;Ehret et al, 2006;Kim and Manini, 2008;Piguet et al, 2004;Reddy et al, 2010). Other risk factors such as the concurrent use of CYP450 isoenzyme inhibitors and hepatic insufficiency, which result in an increase in the plasma concentration of methadone, have also been suggested to contribute to QTc prolongation (Piguet et al, 2004).…”
Section: Cyp2c19 Gene In Methadone Maintenancementioning
confidence: 99%
“…15 Methadone is metabolized primarily in the liver into inactive metabolites by the P450, CYP 3A4 enzymes that are also used by several QTc prolonging medications. 16,17 Methadone is a weak inhibitor of the 3A4 system and a minor weak substrate of 2C89, 2C19 and 2D6. 16 In methadone-naïve persons, it takes approximately two weeks for enzymatic systems to convert methadone into its inactive metabolites.…”
Section: Pharmacologymentioning
confidence: 99%
“…16,17 Methadone is a weak inhibitor of the 3A4 system and a minor weak substrate of 2C89, 2C19 and 2D6. 16 In methadone-naïve persons, it takes approximately two weeks for enzymatic systems to convert methadone into its inactive metabolites. 8 Individual differences in methadone metabolism by CYP 3A4 and 2D6 suggest the possibility of drug interactions that may influence sensitivity and risk, especially when methadone is taken in conjunction with drugs that prolong QTc or have respiratory depressive effects on their own.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Added to the above complexities, methadone has been shown to increase the QT interval to potentially dangerous levels and this must be monitored in all patients on this drug. 19 Further, long-term use of opiates places patients with hypoventilation syndromes and sleep apnea at risk. Methadone specifically may increase the risk of development of de novo central sleep apnea as well.…”
mentioning
confidence: 99%